(3OQQ GdHMGQ Ydi GNJdGa GdCFeI GdGQHYs - (3eMeO Hf jhSa Hf EdjGS, TeS GdOjf Gdobhnfphj,J (B788 (3g` s ((3ecI GdeTQaI s)
(3ChdgG (B:s
(3GdMeO ddg GdPi abg bdhH GdeQJSejf HShGHb dhGMb Gdjbjf ai ObGFb MbGFb GdOjf agPG cJGH CQOfG hfMf ePYfhf HCf GdHVGYI eRLGI s
(3BNQgG (B:s
(3hVQH Sge cd aQjb ai hab GdJQcI abSe GdeHdZ Ydi hab GdJUMjM Je cJGH OQQ GdHMGQ Ydi jO SGdcI s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B153 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B122s
Keywords: (3eJaQbGJs